Tari Lenggang Cisadane Di Sanggar Puspa Kencana Sebagai Perwujudan Multikulturalisme Di Kota Tangerang - Yuritsha Indriani Putri; Nursilah; Kartika Mutiara Sari (Program Studi Pendidikan Tari FBS UNJ, 2025)
Lenggang Cisadane Dance is a traditional dance of Tangerang City that reflects the cultural diversity of its people. This dance emerged as a fusion of various cultural elements, including Sundanese, Betawi, Malay, and Chinese influences, making it a symbol of multiculturalism in Tangerang City. This study aims to analyze how Lenggang Cisadane Dance represents multicultural values and how dance can serve as a medium to strengthen social harmony in a diverse society. This research employs an ethnographic method with a qualitative approach. Data was collected through observations, interviews, and document studies at Sanggar Puspa Kencana, the primary institution for teaching this dance. The data analysis process includes data reduction, data presentation, and conclusion drawing. The results indicate that Lenggang Cisadane Dance embodies three main principles of multiculturalism: recognition of diversity, respect for individual rights, and dialogue and interaction. The elements of movement, music, and costumes in this dance demonstrate a harmonious blend of cultures. Thus, Lenggang Cisadane Dance is not only a form of performing art but also an educational tool and an effective medium for intercultural interaction in Tangerang City.